2014
DOI: 10.1089/thy.2013.0308
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Differentiated Thyroid Cancer by Socioeconomic Status and Urban Residence: Canada 1991–2006

Abstract: Our study confirmed a dramatic increase in thyroid cancer incidence in Canada. Thyroid cancer incidence was significantly higher in higher InQs and in cities. These data support the theory that increased access to imaging is largely responsible for this increased incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 7 publications
8
35
0
Order By: Relevance
“…3 A relationship between race, higher education level, urban residence, location around a metropolitan area, and higher socioeconomic status, which all allow better healthcare access, and a higher incidence of well-differentiated thyroid cancer has been found, even in healthcare systems with no barriers to access. 65,[99][100][101][102] In South Korea, the incidence of welldifferentiated thyroid cancer is 55% lower in the low-income group in comparison with high income. 103 Morris et al 104,105 found that 25% of the incidence can be explained by variables associated with better healthcare access.…”
Section: Economic and Medicolegal Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A relationship between race, higher education level, urban residence, location around a metropolitan area, and higher socioeconomic status, which all allow better healthcare access, and a higher incidence of well-differentiated thyroid cancer has been found, even in healthcare systems with no barriers to access. 65,[99][100][101][102] In South Korea, the incidence of welldifferentiated thyroid cancer is 55% lower in the low-income group in comparison with high income. 103 Morris et al 104,105 found that 25% of the incidence can be explained by variables associated with better healthcare access.…”
Section: Economic and Medicolegal Issuesmentioning
confidence: 99%
“…Epidemiologic evidence from cancer registry analyses showed that the increase in well‐differentiated thyroid cancer was higher in developed countries (12/100 000 in Israel and 10/100 000 in the United States vs 1.5/100 000 in Uganda and 2.6/100 000 in Egypt) where access to the healthcare system is better . A relationship between race, higher education level, urban residence, location around a metropolitan area, and higher socioeconomic status, which all allow better healthcare access, and a higher incidence of well‐differentiated thyroid cancer has been found, even in healthcare systems with no barriers to access . In South Korea, the incidence of well‐differentiated thyroid cancer is 55% lower in the low‐income group in comparison with high income .…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer is the endocrine malignancy 1 that, although stable until the 1990s, has progressively and greatly increased thereafter 2, 3 . The vast majority of the thyroid cancers originate from the follicular cell epithelium 1 , which includes papillary thyroid carcinoma (PTC) that accounts for approximately 80% of all thyroid malignancies 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer incidence, stable until the early 1990s, has continuously and dramatically increased thereafter (Howlader et al, 2013;Guay et al, 2014). During the same period, most cancers have decreased and no cancer has increased as much as thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%